The Synergistic Effect of Aspirin and Brassinolide Hormone in Some Enzymatic and Non-enzymatic Antioxidants of Caraway Plant (Carum carvi) Exposed to Water Stress - Hayder Nasser Hussain Al-Mentafji (Journal of Global Pharma Technology, 2019)
The experiment was conducted to study was the effect of water stress (5,10,15) days and interaction with spraying Aspirin (ASA) (0,5,10) mg.L-1 and brassinolide (BL) growth regulator (0,0.5,1) mg.L-1 on some biochemical and enzymatic and non-enzymatic antioxidants (Salicylic acid concentration, Carotene concentration, Phytosterols, Glutathione Peroxidase (GPX) Enzyme Activity, Glutathione (GSH) concentration) and the and the Free radicals scavenging activity for Caraway plant Carum carvi, the experiment performed with factorial Randomized Block Complete Design (RBCD), with three replicates and 81 experimental units the area of one of them 2m2.The Results Showed:The effect of severe water stress for 15 days was negative effect and decreased the means of studying characters.Increasing in the GPX activity and GSH means under Water stress and spraying with (Aspirin, Brassinolide)The means of free radicals scavenging activity decreased with water stress.The effect of aspirin and brassinolide was positive to increase of study characters with the influence of concentrations under water stress.The role of aspirin and brassinolide were positive to decrease of passive effect of water stress also the triple interaction between the severe stress at 14 days and then spraying the aspirin and hormone was positive to decrease the effect of severe stress.Keywords: (Water stress, Aspirin, Brassinolide, Carum carvi).